What if We Adopt a Resilience Thinking Approach in the Urban Governance for Emission Reduction? - Giulia Sonetti (European Regional Science Association (ERSA), 2015)
In recent times, the contribution of technology and standard energy indicators in urban governance for a wiser use of energy resources has been called in debate, emphasising the potential role of traditional ecological knowledge, individual lifestyles, and in general a wider long-term thinking about the sustainability goal of policy makers. A resilience perspective may help in exploring the contribution of community resilience when dealing with human factors and energy consumptions trends. The paper analyses these relations by observing a special portion of city represented by university campuses. In particular, energy data from the Sustainability Office of the Hokkaido University, in Japan, coupled with surveys with campus users in the effort to reduce their energy consumption, are red under a resilience lens. Results showed that although collective responses did produce sparkling and virtuous outcomes, there were not enough to reach the targets fixed by the national government in terms of electric and thermal energy percentage reduction. Conclusions outline the possibility of systematic efforts to break through the current curricular paradigms in reducing public building energy consumption, using new ways to foster cultural identity protection and resilience thinking in urban governance action toward a low carbon society.
Keywords: 330; Sustainability Assessment; University Campus; Community Resilience